Etude de l’activité antimicrobienne des extraits de Syzygium aromaticum et Linum usitatissimum. - KACHER, Affaf; HANSALI, Hana (My University, 2020)
The excessive use of antibiotics is an important factor that contributes to the appearance of different types of resistant microbes. Consequently, this phenomenon leads to an increase in the severity of the diseases caused by these microbes, which necessitates the search for solutions to this problem. The aim of present study was to evatuate the antimicrobial activity of two medicinal plants : cloves (Syzygium aromaticum) and flax seeds (Linum usitatissimum) and to expose their medical role on the health of Man. In the experimental part : various scientific works were presented and which carried out antimicrobial tests of the two spices : cloves and flax seeds by method of diffusion on disc in solid medium. These tests were carried out on various microbial germs, the main ones being : Candida albicans, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Bacillus cereus. Several plant extracts were prepared from the two plants, the most effective of which were : aqueous extract and methanolic, ethanolic, ethyl acetate and butanol extracts. The results showed a strong inhibitory effect of the methanolic extract of cloves against Staphylococcus aureus with a zone inhibition of 24 mm. The results also showed a very important antimicrobial activity by the aqueous extract of flax seeds against Staphylococcus aureus with a zone inhibition of 1.8 cm. Syzygium aromaticum and Linum usitatissimum exhibit impressive natural antimicrobial activity which can significantly impede microbial development and which can be an effective alternative to antibiotics. The inhibitory effect of these two plants on bacterial and fungal development suggests prospects for application in the medical field.
Keywords: Syzygium aromaticum; Linum usitatissimum; Microbes; Antimicrobial activity; inhibitory effect.